Effect of Agricultural Financing on the Performance of Agricultural Sector in Nigeria - Obioma I. F.; Ihemeje J. C.; Ogbonna C. I.; Amadi C. O.; Hanson U. E (Journal La Bisecoman, 2021)
The study examined the effects of agricultural financing on the performance of agricultural sector in Nigeria using annual time series data. The data for the study was sourced from the Central Bank of Nigeria (CBN) Statistical Bulletin. Contribution of agriculture to GDP was used as proxy for the performance of agricultural sector, commercial banks loan to agriculture, rain fall, government expenditure to agriculture and interest rate were used as proxy for explanatory variables. Following unity in the order of integration, Johansen cointegration approach was used to check for the long run relationship among the variables. Vector autoregressive estimate the vector correction mechanism was used to examine the speed of adjustment of the variables from the short run dynamics to the long run equilibrium. The study found that there is long run relationship among the variables. Specifically; there is significant and long run effect of Agricultural Credit Guarantee Scheme on Contributions of agriculture to GDP. Commercial banks loans to agriculture showed positive and significant effect on Contributions of agriculture to GDP within the reference period. The coefficient of multiple determinations explained the variation in the dependent variable jointly explained by the independent variables. The study recommend that there should be increase in the amount which the agricultural credit guarantee scheme inject into the sector on annual basis and proper supervisory measures should be constituted in order to ensure efficient application and use of the money.